‘Où peut-on être mieux?’ Masonic music and musicians in 19th-century Brussels - Vergauwen, David (2014)
The researcher David Vergauwen has defended a PhD-thesis, entitled “‘Où peut-on être mieux?’ Masonic music and musicians in 19th-century Brussels” at the Free University of Brussels (VUB) in Belgium the 21st of May 2014.